Pengaruh Pengelolaan Kualitas Layanan Melalui Program Pertamina Way Terhadap Kepuasan Konsumen Dan Dampaknya Pada Citra SPBU Pertamina (Studi Pada SPBU Pasti Pas Di Surabaya) - Sri Setyo Iriani, ; Puguh Yulianto, (Bisnis dan Manajemen, 2010)
Since 2007, BBM industry retail in Indonesia has been entered free trade. This make Pertamina do service quality management to entire SPBU Pertamina through Pertamina Way Program. Pertamina way is five standard operational elements which have to be reached by every SPBU Pertamina for consumers. Five elements its self consisted of: 1) Well trained and motivated staff, 2) quality and quantity assurance, 3) well-maintained equipment and facility, 4) consistent physical format, 5) as well as product offerings and value-added services. Service quality in this study is measured by dimensions of retail service quality according to Dabholkar, et al (1996) is consisted of: physical aspects, reliability, personal interaction, problem solving, and policy. This research purpose are: 1) to determine consumer perceptions of service quality at SPBU Pertamina with Pasti Pas logo in Surabaya, 2) to determine the influence of service quality management through Pertamina Way program to consumer satisfaction SPBU Pertamina with Pasti Pas logo in Surabaya, 3) to determine whether consumer satisfaction will have an impact on the brand image of SPBU Pertamina in Surabaya, 4) to determine the influence of service quality management through Pertamina Way programs is influenced to the brand image of SPBU Pertamina in Surabaya. The sample in this study is the consumer of 48 SPBU Pertamina Pasti Pas logo in Surabaya is consisted of 200 respondents. Sample decision techniques used non probability sampling with accidental sampling method and quota sampling. Data analysis technique used Structural Equation Modeling (SEM) by software AMOS 16.0 and SPSS 16.0. From the results of the analysis note that: 1) consumer have a positive perception of service quality at SPBU Pertamina with Pasti Pas logo in Surabaya, 2) service quality management is influenced significantly to consumer satisfaction of SPBU Pertamina with Pasti Pas logo in Surabaya, 3) customer satisfaction does not affect significantly to the image of SPBU Pertamina in Surabaya, 4) service quality management is influenced significantly to the image of SPBU Pertamina in Surabaya.